The letters of George Santayana. - Santayana, George, 1863-1952 (Santayana, George, 1863-1952. Works. 1986 ;, 2008)
Letters from the last years of Santayana's life, written as he completed Dominations and Powers, the final volume of his autobiography, and the one-volume abridgement of his early five-part masterwork, The Life of Reason. This final volume of Santayana's letters spans the last five years of the philosopher's life. Despite the increasing infirmities of age and illness, Santayana continued to be remarkably productive during these years, working steadily until September 1952, when he died of stomach cancer, just three months short of his eighty-ninth birthday. Still living in the nursing home run by the "Blue Sisters" of the Little Company of Mary in Rome (now with such prewar luxuries as hot baths and central heating restored), Santayana completed his book Dominations and Powers, which had been more than fifty years in the making, the final part of his autobiography Persons and Places, published posthumously in 1953 as My Host the World, and the abridgement of his early five-part masterwork, The Life of Reason, into a single volume--all while continuing to maintain a voluminous correspondence with friends and admirers. The eight books of The Letters of George Santayana bring together over 3,000 letters, many of which have been discovered in the fifty years since Santayana's death. Letters in Book Eight are written to such correspondents as the young American poet Robert Lowell (whom Santayana thinks of "only as a friend and not merely as a celebrity" and to whom he sends a wedding gift of $500); Ira D. Cardiff, the editor of Atoms of Thought, a collection of excerpts from Santayana's writings (which, Santayana complained, portrayed him as more akin to Tom Paine than Thomas Aquinas); Richard Colton Lyon, a young Texan who would later collect Santayana's writings about America in Santayana on America: Essays, Notes, and Letters on American Life, Literature, and Philosophy (1968); and the humanist philosopher Corliss Lamont